Putting PPs into order - Understanding prepositionality in the predominantly postpositional language Lule Sami - Ajer, Hanna Danbolt (University of Cambridge, 2023)
This thesis investigates PP-internal word-order variation in an endangered Uralic language, Lule Sami, which is indigenous to parts of Northern Norway and Sweden. The study focuses on the factors underlying prepositional occurrences in this predominantly postpositional language. It is mainly based on spoken data containing more than 4,000 occurrences of adpositions, elicited from eleven native speakers of Lule Sami in Divtasvuodna/Tysfjord, the Lule Sami heartland in Norway. The study aims to contribute to our knowledge of Lule Sami, which is severely understudied. I argue that prepositionality in this language can mark that (part of) the PP is either contrastive or belongs to a system of conventionalised alternatives, which I term a PREDEFINED ALTERNATIVE SET. The findings from Lule Sami may be relevant to the study of related languages as well, as there appear to be many similarities with other Sami languages and Finnic languages. Furthermore, in identifying factors related to semantics and information structure which may influence word order in the PP, and in seeking to account for the variation formally, it is hoped that the study might more generally add to our understanding of AMBIPOSITIONS – adpositions with variable word order (Libert 2006). Lastly, the study highlights the importance of studying variation in endangered languages on its own terms, as the systematic nature of the PP-internal word-order variation in Lule Sami and the similarities with related languages suggest that the prepositional usages cannot simply be attributed to influence from prepositional contact languages. Chapter 1 provides background information about Lule Sami language and history, whereafter chapter 2 outlines the theoretical background of this study. This pertains to Lule Sami grammar, adpositions in related languages, potentially relevant syntactic, semantic, and information-structural factors, and language contact and change. My methodology is laid out in chapter 3. The data and findings from the study are presented in ...